The Praise of Three Martyrs of Vilnius by Michael Balsamon: A Search for Historical Facts in a Late Byzantine Hagiographical Source - Svarevičiūtė, Kristina (Senoji Lietuvos literatūra, 2014)
The paper addresses Τοῦ ῥήτορος τῆς ἁγιωτάτης τοῦ Θεοῦ μεγάλης ἐκκλησίας Μηχαὴλ τοῦ Βαλσαμῶνος εἰς τοὺς ἁγίους καὶ ἐνδόξους νεοφανεῖς μάρτυρας Ἀντώνιον, Ἰωάννην καὶ Εὐστάθιον τοὺς ῥώσσους (The Praise of the New Holy and Glorious Martyrs, the Russians Anthony, John and Eustatia) that Michael Balsamon wrote in Byzantium in the late 14th century, in order to discover whether this is a reliable historical source, and what facts about the torturers the work reveals. The paper begins with an overview of the periodization of Byzantine hagiography and a discussion of its main features, with a focus on the Palaeologan period. It proceeds to the analysis of the structure and style of the source, and then focuses on the analysis of the semantic aspects of the lexis which we are particularly interested in. The paper, which emphasizes the aspects of analysis of a source characteristic of a particular period and genre and the results obtained, enters into a polemic with the historian Darius Baronas. Finally, the author arrives at the conclusion that the literary quality of the work gives no cause for any doubt. Its schematic structure and literary means make it possible to consider it a source of late Byzantine high literature; the lexis of abstract meaning and abundant synonyms impart abstract and literary characteristics to the text. Meanwhile, actual historical facts that do not raise doubts are not numerous, and the lexis used does not make it possible to link the torturer with a particular individual.
Keywords: -